Pathophysiology, Evaluation, and Management of Edema in Childhood Nephrotic Syndrome - Ellis, Demetrius (Frontiers in Pediatrics, 2016)
Generalized edema is a major presenting clinical feature of children with nephrotic syndrome (NS) exemplified by such primary conditions as minimal change disease (MCD). In these children with classical NS and marked proteinuria and hypoalbuminemia, the ensuing tendency to hypovolemia triggers compensatory physiologic mechanisms which enhance renal sodium (Na+) and water retention; this is known as the “underfill hypothesis”. Edema can also occur in secondary forms of NS and several other glomerulonephritides, in which the degree of proteinuria and hypoalbuminemia, are variable. In contrast to MCD, in these latter conditions the predominant mechanism of edema formation is “primary” or “pathophysiologic”, Na+ and water retention; this is known as the “overfill hypothesis”. A major clinical challenge in children with these disorders is to distinguish the predominant mechanism of edema formation, identify other potential contributing factors, and prevent the deleterious effects of diuretic regimens in those with unsuspected reduced effective circulatory volume (i.e., underfill). This article reviews the Starling forces that become altered in NS so as to tip the balance of fluid movement in favor of edema formation. An understanding of these pathomechanisms then serves to formulate a more rational approach to prevention, evaluation and management of such edema